11.63: Seismic protection of gas tanks. (13th September 2017) - Henriques, Jose; Morelli, Francesco; Salvatore, Walter; Degée, Hervé
ABSTRACT: Recent earthquakes demonstrated the susceptibility of industrial plants to such events. In extreme situations, as the earthquake in Fukoshima (Japan), the impact of the seismic action on these infrastructures leads to catastrophic results with consequences for the environment, neighbour population and economy. The impact of an earthquake on an industrial plant may result in a local failure, leading to an interruption on the operation, or a total collapse. In any of these cases, it is imperative the improvement of such facilities with high importance class. It is to this end that the European project PROINDUSTRY is ongoing. The objective is the development of innovative seismic protection systems for industrial buildings or infrastructures made of steel. In the present paper the numerical study of a gas tank is presented. For this type of infrastructures, amongst the different devices under development, the base isolation system was selected as it is seen as the most suitable. The proposed device is the Curved Surface Slider (CSS). In order to evaluate the performance of such device, numerical studies, namely Incremental Dynamic Analysis, were conducted. The results of these analyses lead to a calibration of the main properties of this device, static friction and vibration period, and allowed to verify the effective protection of the gas tank upon an earthquake event.